Growth Promotion and Disease Suppression Ability of a Streptomyces sp. CB-75 from Banana Rhizosphere Soil - Chen, Yufeng; Zhou, Dengbo; Qi, Dengfeng; Gao, Zhufen; Xie, Jianghui; Luo, Yanping (Frontiers in Microbiology, 2018)
An actinomycete strain, CB-75, was isolated from the soil of a diseased banana plantation in Hainan, China. Based on phenotypic and molecular characteristics, and 99.93% sequence similarity with Streptomyces spectabilis NBRC 13424 (AB184393), the strain was identified as Streptomyces sp.. This strain exhibited broad-spectrum antifungal activity against 11 plant pathogenic fungi. Type I polyketide synthase (PKS-I) and non-ribosomal peptide synthetase (NRPS) were detected, which were indicative of the antifungal compounds that Streptomyces sp. CB-75 could produce. An ethyl acetate extract from the strain exhibited the lowest minimum inhibitory concentration (MIC) against Colletotrichum musae (ATCC 96167) (0.78 µg/ml) and yielded the highest antifungal activity against Colletotrichum gloeosporioides (ATCC 16330) (50.0 µg/ml). Also, spore germination was significantly inhibited by the crude extract. After treatment with the crude extract of Streptomyces sp. CB-75 at the concentration 2 × MIC, the pathogenic fungi showed deformation, shrinkage, collapse, and tortuosity when observed by scanning electron microscopy (SEM). By gas chromatography-mass spectrometry (GC-MS) of the crude extract, 18 chemical constituents were identified; (Z)-13-docosenamide was the major constituent. Pot experiments showed that the incidence of banana seedlings was reduced after using Streptomyces sp. CB-75 treatment. The disease index was 10.23, and the prevention and control effect was 83.12%. Furthermore, Streptomyces sp. CB-75 had a growth-promoting effect on banana plants. The chlorophyll content showed 88.24% improvement, the leaf area, root length, root diameter, plant height, and stem showed 88.24%, 90.49%, 136.17%, 61.78%, and 50.98% improvement, respectively, and the shoot fresh weight, root fresh weight, shoot dry weight, and root dry weight showed 82.38%, 72.01%, 195.33%, and 113.33% improvement, respectively, compared with treatment of fermentation broth without Streptomyces sp. CB-75. Thus, Streptomyces sp. CB-75 is an important microbial resource as a biological control against plant pathogenic fungi and for promoting banana growth.